Pedagogical and Professional Competence of Islamic Religious Education Teachers in the Perspective of Technological Pedagogical and Content Knowledge (TPACK): A Comparative Study at MAN 2 Sleman and MAN 2 Bantul - ’Abid, Muhammad Husnul; Nailasariy, Asniyah; Khuzaifah, Khuzaifah (Kalijaga Journal of Islamic Religious Education, 2025)
This study was motivated by the importance of integrating content knowledge, pedagogy, and technology (TPACK) in learning, especially for Islamic Religious Education (IRE) teachers. The purpose of this study was to analyze the extent to which IRE teachers at MAN 2 Sleman and MAN 2 Bantul integrated pedagogical, professional, and technological competencies in the learning process. This study used a field design with a descriptive qualitative approach. There were four informants selected through purposive sampling, while data were collected through non-participant observation, semi-structured interviews, and documentation. The analysis was conducted using the Miles and Huberman interactive model and triangulation of sources and techniques to test the validity of the data. The results showed that IRE teachers at MAN 2 Sleman and MAN 2 Bantul had implemented the TPACK framework well, as reflected in their ability to design learning, understand student characteristics, master teaching materials, and utilize technology in an integrative manner. This implementation was supported by the availability of technological facilities, school policies, teacher capabilities, student support, and professional training, but still faced obstacles such as limited technological skills, infrastructure, time, and internet connectivity. This study recommends strengthening IRE teacher technology training and improving digital facilities.